The Effect of Tapioca Flour Substitution with Purple Sweet Potato Flour (Ipomoea batatas Blackie) on the Organoleptic Testing of Beef Meatballs - Wijayanto, Sandy; Rahmawati, Resti Yuliana; Samur, Salnan Irba Novaela (Universitas Veteran Bangun Nusantara, 2025)
The increasing demand for processed meat products has driven innovation toward offerings that are not only delicious and practical but also more nutritious. Beef meatballs are among the most popular processed meat products, but they often contain tapioca flour as a filler, which is low in fiber and antioxidants. This study aimed to evaluate the effect of substituting tapioca flour with purple sweet potato (Ipomoea batatas blackie) flour on the organoleptic quality of beef meatballs. The research was conducted in April 2025 at the laboratory of Universitas Islam Balitar using a completely randomized design (CRD) with four treatments and three replications: p0 (no substitution), p1 (10 g substitution), p2 (20 g substitution), and p3 (30 g substitution) of purple sweet potato flour. Organoleptic tests were carried out on color, aroma, taste, and texture parameters by 30 untrained panelists using a 1–4 hedonic scale. The results showed that purple sweet potato flour substitution had a significant effect (p<0.05) on all organoleptic parameters. p1 produced the highest scores for color (2.61) and taste (2.66), while the best texture was obtained in p3 (2.59). The highest aroma score was found in p0 (2.66). The trend indicated that increasing the concentration of purple sweet potato flour tended to decrease color, taste, and aroma scores, while texture tended to improve. Therefore, substitution up to 10% purple sweet potato flour was the optimal proportion that remained acceptable to consumers in terms of organoleptic aspects. This study highlights the potential use of local antioxidant-rich ingredients to enhance the functional value of processed meat products such as meatballs.